VD_FINDINFO ML / 2014 / 64 vom 10. April 2014 - VD Tribunal cantonal (2014)
DROIT D'ÊTRE ENTENDU, NOTIFICATION IRRÉGULIÈRE, NULLITÉ | 29 al. 2 Cst., 136 CPC (CH), 138 CPC (CH), 253 CPC (CH), 53 CPC (CH)